Water as a Weapon and Bridge: Pakistan’s Transboundary Diplomacy in the Indus Basin - Ms. Najma Naz; Ms. Nusrat Khaskheli; Shafique Husssain Wassan (Journal of Religion and Society, 2025)
This article examines Pakistan’s transboundary water diplomacy in the Indus Basin through the conceptual lens of water as both a weapon and a bridge, highlighting the interplay between conflict and cooperation in one of the world’s most politically sensitive river systems. It situates water within the broader framework of international relations, emphasizing its growing significance as a strategic resource shaped by geopolitical tensions, institutional arrangements, and environmental pressures. The study explores the historical and legal foundations of Indus Basin governance, focusing on the Indus Waters Treaty as a durable yet evolving mechanism that has enabled sustained engagement between Pakistan and India despite recurring conflicts. It further analyzes the securitization of water in Pakistan’s foreign policy discourse, where upstream developments and hydropower projects are often perceived as threats, contributing to a narrative of vulnerability and strategic competition. At the same time, the article highlights the cooperative dimensions of water diplomacy, including institutional mechanisms, confidence building measures, and the role of international actors in facilitating dialogue and dispute resolution. By integrating insights from hydro political theory, environmental diplomacy, and international law, the study demonstrates that water governance in the Indus Basin is characterized by a dynamic balance between rivalry and collaboration. It argues that Pakistan’s diplomatic approach reflects both the constraints of its downstream position and the opportunities presented by institutionalized cooperation, particularly in the context of climate change and increasing resource scarcity. The article concludes that the future of transboundary water relations in the region will depend on the capacity of states to adapt existing frameworks, strengthen cooperative mechanisms, and reconceptualises water as a shared asset rather than a contested resource. Keywords: Transboundary Water Diplomacy, Indus Basin, Pakistan Foreign Policy, Water Securitization, Environmental Cooperation, Indus Waters Treaty